BOHEMIAN RHAPSODY MOVIE: AN ANALYSIS OF FLOUTING MAXIM - Putra, I Komang Agus Astina; Suastini, Ni Wayan; Resen, I Wayan (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2023)
The present research focuses on flouting maxim in Bohemian Rhapsody movie. The aim of this research is to find out the types of flouting maxim found in Bohemian Rhapsody movie. The data were taken from the Bohemian Rhapsody movie that has been downloaded and they are collected through observation and taking note technique. In this research, the researcher focused on the theory of Grice (1975) in analysing the type of flouting maxims. The descriptive qualitative method was used in analysing the data found in this research. In analysing the data, the researcher used the theory from Grice (1975) about Logic and conversation. Based on Grice theory (1975) “flouting maxims belong to the form of non-observe conversation principle”. The result of the research shows that the types of flouting maxim found in the movie are 44 data. The dominant flouting maxim did by the characters in this movie is the flouting maxim of manner with the frequency of 15 data (34%), following by flouting maxim of quality with frequency of 12 data (27%), next is flouting maxim of quantity with frequency 9 data (21%), and the last one flouting the maxim of relevance which is the type of flouting maxim that occurs the least in this Bohemian Rhapsody movie with a frequency of 8 data (18%). From the data that has been got in the Bohemian Rhapsody movie, the character who does the most flouting the maxim is the main character in this movie, Freddie Mercury did all types of floating the maxim. Keywords: Flouting maxim, Bohemian Rhapsody, Types of flouting maxim